2021
DOI: 10.1021/acsaem.1c02283
|View full text |Cite
|
Sign up to set email alerts
|

Insights into Gas-Exfoliation and the In-Situ Template Mechanism of Zinc Compound for Lignin-Derived Supercapacitive Porous Carbon

Abstract: The large-scale production of porous activated carbon is plagued by the overuse of corrosive activators, so developing a green and mild activation strategy is technologically urgent and meaningful. Herein, two gentle activators (ZnCO 3 and ZnC 2 O 4 ) and a traditional corrosive agent (ZnCl 2 ) are utilized to activate lignin for porous carbons, and the microstructures and electrochemical properties of the carbons are systematically investigated. By tracking the evolution of the carbonized products through TG-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 17 publications
(5 citation statements)
references
References 45 publications
0
5
0
Order By: Relevance
“…Therefore, tremendous efforts have been made to develop green and efficient technologies for the production of PLCs. [ 66–69 ]…”
Section: Application Of Lignin Carbons In Electrochemical Energy Storagementioning
confidence: 99%
See 2 more Smart Citations
“…Therefore, tremendous efforts have been made to develop green and efficient technologies for the production of PLCs. [ 66–69 ]…”
Section: Application Of Lignin Carbons In Electrochemical Energy Storagementioning
confidence: 99%
“…Meanwhile, the symmetric supercapacitor assembled with this carbon electrode exhibited high energy densities of 11.84 and 66.18 Wh kg −1 in 6 M KOH and ionic liquid electrolytes, respectively (Figure 8c). Yang et al [ 67 ] proposed an in‐situ gas exfoliation and template method to prepare PLC with high mesoporosity. It was found that ZnCO 3 and ZnC 2 O 4 have dual functions of activation and template.…”
Section: Application Of Lignin Carbons In Electrochemical Energy Storagementioning
confidence: 99%
See 1 more Smart Citation
“…By tracking the evolution of the carbonized products through mass spectrometry, in situ FTIR, and other characterization methods, the gas-exfoliation and in situ template functions of zinc carbonate and zinc oxalate were proposed by Fu and coworkers, who found that the pyrolysis synergistic effect boosts the decomposition of oxygen-containing groups, playing a pivotal role in the fabrication of hierarchical porous carbon with crumpled nanosheets [ 144 ].…”
Section: Applications To Cellulose Lignin and Lignitementioning
confidence: 99%
“…Owing to gas exfoliation and in-situ ZnO template roles of ZnC 2 O 4 during the carbonization process, porous LDPC quasi-nanosheets with a SSA of 1069 m 2 g −1 and a total pore volume of 1.375 cm 3 g −1 were obtained(Fu et al 2020). Furthermore, Fu et al investigated the effects of ZnCO 3 and ZnC 2 O 4 on the structure of LDPC, and concluded that ZnC 2 O 4 had a synergistic effect with lignin, playing a key role in the preparation of hierarchical porous carbon with crumpled nanosheets(Fu et al 2021).…”
mentioning
confidence: 99%